ANALISIS PENGARUH KARAKTERISTIK INDIVIDU TERHADAP PRESTASI KERJA (STUDI PADA PEGAWAI POLITEKNIK ILMU PELAYARAN SEMARANG) - Firdaus Sitepu; Janny Adriani Djari (Dinamika Bahari, 2017)
This research aim to know individual characteristic influence to labour capacity Politeknik Ilmu Pelayaran Semarang. Research regarding do individual characteristic influence intervening motivation and work characteristic to labour capacity take population officer of Politeknik Ilmu Pelayaran Semarang amounting to 218 people. Intake of sample with sampling random technique representing technique intake of sample at random with determination of is amount of sampel used by slovin formula obtained by 142 responder. As for data obtained with kuesioner with data analysis use linear regression. Pursuant to research which have been done by hence can be obtained by the following conclusion is existence of positive influence and signifikan between individual characteristic to labour capacity.